Investigation of tryptophan fluorescence as a tool for the analysis of oligomerisation and folding of antimicrobial peptides and lysozyme - Maya Kamila Dibyana (2025)
Despite ongoing medical advancements and widespread use of antibiotics, bacteria continue to cause serious infections all over the world, necessitating the need for alternatives. Antimicrobial peptides (AMPs) have raised interest for a new development of drugs and one of the main advantages of this class of molecules is their activity against wide range of microorganisms including bacteria, fungi, viruses and even tumor cells. By focusing on recent insights into the folding and oligomerization of AMPs can yield information into their mechanism of action such as their interactions with bacterial membrane. Tryptophan fluorescence measurements is used to investigate the oligomerisation of AMPs since the structure of AMPs that were analyzed on this paper have tryptophan residues which are classified as hydrophobic amino acid. The fluorescence of tryptophan exhibits an increase in intensity when the hydrophobicity of the surrounding environment rises. A shift towards shorter wavelengths, known as a blue shift, is